PRODUKSI BIOINSEKTISIDA oleh Bacillus thuringiensis MENGGUNAKAN KULTIVASI MEDIA PADAT - Rini Purnawati, Titi C. Sunarti Khaswar Syamsu, Mulyorini Rahayuningsih (Jurnal Teknologi Industri Pertanian, 2015)
*Penulis untuk korespondensi In bio insecticide production, the use of agricultural by products as a substrate to produce the starter has the role important on the efficient production processes, as well as the use of single isolate and production media. The bio insecticide production was carried out by the solid state cultivation, by examining the effect of substrate thick nessoncell growth and bio insecticide toxicity of bio insecticide produced. The bacterial of localisolates used were obtained from carrion worm of Attacus atlas, and identified as Bacillus thuringiens is and had  important potential as bio insecticide. Tofu whey was used for starter media, while mixture of dregs sago and iles-iles as its production media. During the cultivation the media thickness affected on pH, cell growth, spores and substrate consumption. The increased of substrate thickness caused the decrease of  pH, and  simultaneously the decrease of  cell growth, spores and substrate consumption.  The product with highes toxicity capability against dipteralarvae (LC50 of 0,24 mg/mL) and lepidoptera larvae (LC50 of 3,3 mg/mL) was obtained under cultivation process with substrate thicknes of 1 cm. Keywords: Bacillus thuringiensis, bioinsecticide, solid-state cultivation,  solid waste sago, solid waste iles-iles